Post vs. Post-less Hip Arthroscopy: A Comparison of Traction Force and Patient Specific Parameters. Issue 7 (30th July 2021) - Dowdle, Spencer; Adeyemi, Temitope; Cassidy, Benjamin; Craig, Matthew; Aoki, Stephen; Maak, Travis
Objectives: Hip distraction during arthroscopic surgery has typically utilized a peroneal post, which has known complications; post-less distraction has thus recently gained favor. This study quantified the traction force required for adequate hip distraction during post-less arthroscopic surgery and compared the data to a previous post cohort including the relationship between force and patient-specific factors. Methods: One-hundred thirty-four patients undergoing primary hip arthroscopy were prospectively enrolled. Twenty-nine patients underwent post-less primary hip arthroscopy. A load-cell attached to the traction boot measured traction force. Fluoroscopic images were obtained to measure joint displacement. The stiffness coefficient was calculated as the force of traction divided by joint displacement. Relationships between the stiffness coefficient and patient specific factors were investigated using a univariable regression model. Variables significant at P<0.05 were included in a multivariable regression model. Results: The mean age for the combined cohort was 31.9 ± 8.6 years, 42.5% (57/134) were male, and mean BMI was 24.8 ± 4.3kg/m2. There was no significant difference in age (32.5 ± 8.4 vs. 29.7 ± 9.0; p=0.12), sex (43.8% male vs 37.9% male; p=0.57), or BMI (24.6 ± 4.1 vs. 25.2 ± 5.1; p=0.51) between the posted and post-less cohorts. Both maximum and final traction force and hip distraction were statistically significantly smaller in the post-less traction group (Table 1). In univariable regression analysis for maximum traction force (K-max), post-less traction, male sex, BMI, alpha angle, Beighton score greater than zero, and hamstring flexibility were significant. For final traction force (K-hold), male sex, BMI, alpha angle, Beighton score greater than zero and hamstring flexibility were significant (Tables 2 and 3). In the multi-variate analysis for (1) K-max, five variables remained significant including, posted vs. post-less, sex, hamstring flexibility, alpha angle and Beighton score, and (2) K-hold, three variables remained significant including, posted vs. post-less, sex, and alpha angle (Tables 2 and 3). Conclusions: Maximal and maintained holding distraction forces were significantly lower in the post-less cohort. Female gender, hamstring flexibility lower alpha angle and Beighton score were found to decrease the maximal force needed for hip distraction. Female gender and lower alpha angle were found to decrease the force needed to maintain distraction. The presence of a labral tear did not correlate with distraction force. These data may be used to identify patients in whom a specific focus on capsular repair and/or plication may be warranted. Moreover, post-less traction may reduce post-related complications by reducing maximal and holding traction forces and perineal pressure.